Analisis Gaya Kepemimpinan Terhadap Motivasi Kinerja Guru SMP Negeri 3 Ombarade Wewewa Tengah - Noknisius B. Dola; Ariance Moda; Kasmirsius Dappa; Ongki Sairo Malo; Nikodemus Tamo Ama; Ktispianus Maghu Ate (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
National education based on Pancasila and the 1945 Constitution of the Republic of Indonesia functions to develop the abilities and forms of character and civilization of a dignified nation in order to make the nation's life more intelligent. The aim of the researcher to be achieved is to find out the implementation of the thematic model of integrated learning at SMP N 3 OMBARADE WEWEWA TENGAH southwest Sumba district, the methods used in the research, research results, conclusions, suggestions and implications of the research.